The Effects of Environment, Society and Governance Scores on Investment Returns and Stock Market Volatility - Meher, Bharat Kumar; Hawaldar, Iqbal Thonse; Mohapatra, Latasha; Spulbar, Cristi; Birau, Ramona (International Journal of Energy Economics and Policy, 2020)
Sustainability reporting and disclosure in India have received a significant attention over the most recent few years propelled to a large extent by investors and policy makers. The Sustainable Business Leadership Forum (SBLF) has been closely working with many firms, owners of the companies and policy makers to single out the relationship between investment and environmental, social and governance (ESG) disclosure. Besides that, SBLF has had a coordinated conversation about the anticipations, concerns, difficulties and realities surrounding ESG estimation. This ESG criteria refers to three important elements which are considered by investors with regards to an ethical impact of firms and sustainable practices. As per the literature companies with higher ESG scores are better investment picks. This paper attempts to assess the volatility and returns of Indian companies and to measure the impact of ESG scores on returns and volatility with the help of panel regression. Keywords: ESG, ESG Scores, Sustainability, Panel Regression, Investment returns. JEL Classifications: D22, G11, G14, G32 DOI: https://doi.org/10.32479/ijeep.9311